Foreign Direct Investment in Nepal: Status and Way Forward - Khatiwada, Yam Kumari (Economic Journal of Nepal, 2021)
Foreign Direct Investment (FDI) has been used by developing countries as an important tool for economic development of the country specially to manage the resource gap between saving and investment, government revenue and expenditure gap, trade gap as well as to enhance knowledge, skill, trade, and entrepreneurship efficiency within the country. Inflow of FDI in Nepal started with the adaptation of economic liberalization since 1990 introducing investment friendly policies and institutions. This paper analyses the situation of FDI inflows in Nepal by various accepts such as country wise, sectors wise, scale wise investment based on available data from 2047 to 2078. It also highlights some of the challenges and the opportunities of FDI in Nepal and finally it has provided some of the recommendation for way forward to create investment friendly environment to increase FDI inflows.  With its all prospects, the article argues that FDI is essential to manage the required resource gap for economic development of Nepal, and to graduate from LDC to developing country by 2030 which is one of the agendas of SDGs.